(untitled) (African Journal of Science, Technology and Social Sciences, 2025)
Hypertension remains the most significant modifiable risk factor for stroke worldwide, accounting for nearly half of all stroke cases. In Kenya, hypertension prevalence has steadily increased, contributing to a high burden of stroke-related disability and mortality. This study investigated the determinants of high blood pressure management among patients with hypertension who developed stroke in MeTRH. Using a mixed-methods convergent design, data was drawn from 80 systematically sampled stroke patient records, 42 stratified sampled healthcare workers, and 10 purposively selected hypertensive stroke patients. Data collection employed medical record checklists, self-administered questionnaires, and interview guides. Quantitative data was analyzed using SPSS V25, and thematic analysis via NVIVO for qualitative interviews and integrated with quantitative findings. The findings revealed, prevalence of hypertension-stroke comorbidity was significantly higher among older adults (mean age= 58.6) and females (67.5%), with poor adherence to treatment and lifestyle modification serving as key risk factors. Healthcare system delivery was constrained by inadequate diagnostic resources, shortages of antihypertensive drugs, and limited provider expertise, with nearly half of healthcare workers reporting less than five years of experience in hypertension management, and only 18.4% identified correct definition of hypertension. No statistically significant association between healthcare delivery and blood pressure control (p=0.308). In conclusion, effective hypertension management is hindered by poor patient adherence, inadequate health system delivery, and insufficient provider experience. Strengthening counselling, standardizing care guidelines, and improving access to diagnostics and affordable medications are recommended. Improving both patient-level and system-level determinants of hypertension control is crucial to reducing stroke burden in resource-limited settings.